ผลของโปรแกรมการสนับสนุนความต้องการของครอบครัวต่อการปรับตัวของสมาชิกในครอบครัวผู้ป่วยบาดเจ็บที่ศีรษะ - เบญจมาภรณ์ วงษ์ไกร (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this quasi-experimental research was to study the effect of the family needs supporting program on adjustment of family members of patients with traumatic brain injury. The sample consisted of 40 family members, and patients with traumatic brain injury admitted to the neurosurgery intensive care unit 1, neurosurgery intensive care unit 2, and trauma intensive care unit at Sappasittiprasong Hospital, Ubonrachatani province. Participants were selected into an experimental group and a control group. The groups were similar in age of family members, relationship between family members with traumatic brain injury patients, and level of consciousness of the patients. The experimental group received a family needs supporting program, while the control group received a conventional care. The research instruments were family needs supporting program developed based on family need concept (Daley, 1984). Instrument used were a demographic data form, and Psychosocial Adjustment to Illness Scale: PAIS (Derogatis, 1986). The instruments were tested for content validity by 8 experts. The reliability of the PAIS were .81. The data were analyzed by using mean, percentage, standard deviation, Kolmogorov-Smirnov test statistic and t-test statistic (Paired t-test and Independent t-test). Results were as follows: 1. The adjustment of family members of patients with traumatic brain injury receiving the family needs supporting program at posttest was significantly higher than that of pretest at the .05 level. 2. The adjustment of family members of patients with traumatic brain injury receiving the family needs supporting program at posttest was significantly higher than those who receiving a conventional care at the .05 level.